The Pathological Findings Following Laparotomy in Hodgkin's Disease - Farrer-Brown, Geoffrey (Nature Publishing Group, 1971)
The pathological findings in 50 patients with Hodgkin's disease following laparotomy for diagnostic purposes are described. Forty-four patients had laparotomy before treatment and within a few months of the original diagnosis, while 6 patients had delayed laparotomies. The Rye histological classification was applied to the original lymph node biopsy, the abdominal lymph node and Hodgkin's tissue in the spleen. The variation in appearance both of these tissues and of the liver biopsies is discussed. IMAGES: